2014
DOI: 10.1111/liv.12520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infection on the prognosis of critically ill cirrhotic patients: results from a large worldwide study

Abstract: Infection is more common in cirrhotic than in non-cirrhotic ICU patients and more commonly caused by Gram-positive organisms, including MRSA. Infection in patients with cirrhosis was associated with higher mortality rates than in non-cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 25 publications
2
78
0
Order By: Relevance
“…A large multicentre epidemiological study reported culture positivity for fungi in 25% of patients with cirrhosis admitted to an intensive care unit (ICU) versus 19% in non-cirrhotic patients [10]. However, the significance of this finding is unclear, as there was no report on the incidence of frank invasive fungal disease (IFD) as opposed to colonization.…”
Section: Introductionmentioning
confidence: 99%
“…A large multicentre epidemiological study reported culture positivity for fungi in 25% of patients with cirrhosis admitted to an intensive care unit (ICU) versus 19% in non-cirrhotic patients [10]. However, the significance of this finding is unclear, as there was no report on the incidence of frank invasive fungal disease (IFD) as opposed to colonization.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cirrhosis is a serious risk factor for hospitalization due to infection and for sepsis-related mortality; in patients with advanced liver disease, prevalence of in-hospital infections amounts to 25-35% and to approximately 60% in patients admitted to the ICU [67][68][69]. In comparison to other ICU patient groups, the presence of liver cirrhosis renders subjects acquiring infections more susceptible to multi-system organ failure due to septic shock [69].…”
Section: Infection And/or Sepsismentioning
confidence: 99%
“…In comparison to other ICU patient groups, the presence of liver cirrhosis renders subjects acquiring infections more susceptible to multi-system organ failure due to septic shock [69]. Overall (listing the types of infections from most to least frequent), cirrhotic patients are prone to develop SBP, urinary tract infections, pneumonia, bacteremia, and skin/soft tissue infections [70].…”
Section: Infection And/or Sepsismentioning
confidence: 99%
“…The systemic inflammatory response syndrome (SIRS) is defined by the presence of at least two of the following criteria: (1) altered temperature, (2) elevated respiratory rate or hyperventilation, (3) tachycardia, and (4) altered white blood cell count (high, low, or immature forms) [67]. Sepsis is the most common cause of mortality in most intensive care units (ICUs) [68]. Due to the hyperdynamic circulation and complications of portal hypertension, the currently accepted clinical definition of SIRS and hence sepsis may not be entirely applicable to patients with cirrhosis or ACLF.…”
Section: Sepsis In Aclfmentioning
confidence: 99%